o.T. 46 Avantgarde-Künstler : Eine Shakespeare Retrospektive von 1988-1993. - Schwaiger, Wolfgang (Salzburg : Galerie Shakespeare, 1993)
Grani, Gerfried ; Lingg, Christoph ; Griseldis Eberhart, Manuela ; Lagos, Mario ; Brandstätter, Reinhold ; Prem, Horst ; Potsch, Christian ; Bozatli, Sinasi ; Faeq, Rasul ; Golznig, Johannes Amadeus ; Weinlich, Caroline ; Schobesberger, Erich ; Grill, Helmut ; Kircher, Markus ; Ferner, Michael ; etc.
o.T. 46 Avantgarde-Künstler : Eine Shakespeare Retrospektive von 1988-1993, Galerie Shakespeare, Salzburg, 1993
boek
Keywords: Shakespeare, William